Component redundancy allocation in optimal cost preventive maintenance scheduling - Siopa, Jorge Miguel Peralta (2015)
This work presents a methodology to assist maintenance teams in defining the maintenance schedule and redundancy allocation that minimise the life-cycle average cost of a system. The minimal data required are three average costs and one reliability function. This methodology is useful in a system design phase, since in this situation data is usually scarce or inaccurate, but can also be applied in the exploration phase. It consists of an adaptation of the classical optimal age replacement method, combined with a redundancy allocation problem. A set of simple illustrative examples covering a variety of operating conditions is presented, demonstrating quantitatively the applicability of the methodology to a range of maintenance optimisation decisions.